Strategy of zakat fund collection in Baitul Mal Aceh Tamiang Regency - Agus Faisal Agus Faisal; Alfiqa Najla (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2022)
Purpose – This study aims to find out how the strategy for collecting zakat funds is carried out by Baitul Mal, Aceh Tamiang Regency and to find out how the implementation of zakat fund collection in Baitul Mal, Aceh Tamiang Regency. Method – The research method used is qualitative research, using data collection techniques through observation, interviews and documentation. The results of this study indicate that: First, socialization of zakat collection is through education providing understanding to the community of prospective muzaki. Second, the creation of a zakat collection unit (UPZ), which is an organization formed by the Amil Zakat Agency at all levels with the task of collecting zakat to serve muzakki. Third, the opening of the zakat receipt counter, namely so that more people pay zakat, donate, and give alms. Fourth, opening a bank account to make it easier for muzaki to pay zakat. Fifth, direct zakat collection is to make it easier for muzakki to pay zakat if they do not have time to come directly to give zakat. Results – The results of the study show that the implementation of the collection of zakat funds carried out by Baitul Mal, Aceh Tamiang Regency, firstly online collection, second zakat collection unit, third zakat pick-up service and fourth paying directly to Baitul Mal. Limitations – This study has limitations in terms of strategies for collecting zakat funds which still tend to be few. Practical Implications – As a practical implication, the results of this study can increase zakat literacy and become input for the government, especially zakat institution organizations in encouraging zakat fund collection strategies in Baitul Mal Aceh Tamiang.